Cho a + b + c = 0 CMR M = N = P với M = a( a + b)( a + c) N = b(b + c)(b + a) P = c(c + a)(c + b) Giúp mik vs

Question

Cho a + b + c = 0 CMR M = N = P với
M = a( a + b)( a + c) N = b(b + c)(b + a) P = c(c + a)(c + b)
Giúp mik vs

in progress 0
Clara 5 tháng 2021-07-29T10:57:07+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-07-29T10:58:09+00:00

    Đáp án:

     

    0
    2021-07-29T10:58:59+00:00

     

    Giải thích các bước giải:

     Ta có:

    $a+b+c=0\Rightarrow\left\{\begin{matrix}
    a+b=-c & \\ 
    b+c=-a& \\ 
    a+c=-b & 
    \end{matrix}\right.$ 

    Lại có:

    $M=a(a+b)(a+c)=a.(-c)(-b)=abc$ $(1)$

    $N=b(b+c)(b+a)=b.(-a)(-c)=abc$ $(2)$

    $P=c(c+a)(c+b)=c.(-b)(-a)=abc$ $(3)$

    $Từ$ $(1),(2),(3)\Rightarrow M=N=P=abc$

    (đpcm)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )